A Cloud Based Architecture for Educational Resource Sharing In Ethiopian HEI - Biniyam, Wondie (ASTU, 2017)
Cloud computing has becomes an adaptable technology in many organization .It represents an important changes in the way information technology is used. Moreover most of the education institutions in the world have become extremely reliant on IT. Universities can take the benefits of cloud based application provided by different services provider and facilitates their staff and students to perform various responsibilities. Using cloud computing, we can share educational resources anywhere, using internet enabled devices. The main aim of this research is to design a cloud based architecture to able to share educational resource in Ethiopian higher education institutions. This study proposes Hybrid cloud platform architecture for sharing of educational resources in the Higher education institutions. The cloud based educational resource sharing architecture (CBERSA) adapts the IBM cloud reference architecture (IBMCRA) and NIST cloud reference architecture to exploit all considerations and features of cloud based software architecture. For the designed architecture a prototype system was implemented using Microsoft window azure platform. The prototype is very interactive and user friendly which have resource sharing and accessing portal. The developed prototype system was validated using 20 respondents in three higher education staff members and the result is presented in tabular, bar graph and pie chart form.
Keywords: Cloud computing, Cloud based architecture, Resource sharing, Software architecture, Higher Education Resource